Penerapan Teknologi Ramah Lingkungan untuk Mengurangi Limbah pada Industri Pengolahan Kayu - Mulyana, Tineke; Wardana, Naura Afifah; Apriani, Isna (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The wood processing industry is a crucial sector that utilizes forest resources to produce various value-added products. In Pontianak City, wood processing industries produce items such as door and window frames, doors, windows, and cabinets. The aim of this study is to identify clean production alternatives for the wood processing industry. The research methods include field studies and descriptive analysis of the production process and the potential waste generated. The production process in Pontianak's wood processing industry includes several stages: receiving and unloading raw materials, cutting wood to the required size, profiling products, smoothing wood surfaces, and final assembly of finished products. Each of these stages has the potential to generate waste, including unused wood scraps, wood dust, and shavings from the smoothing process. This study offers recommendations for clean technologies that can be applied to reduce this waste. These clean technologies include the production of active carbon, using wood dust waste as partition material, producing bio briquettes and wood pellets as alternative fuels, and using wood waste as a growing medium for oyster mushroom cultivation. Additionally, wood waste can be used to create creative products, such as entertainment and educational games.